The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12879-021-06739-8
|View full text |Cite
|
Sign up to set email alerts
|

A Schizophyllum commune fungus ball in a lung cancer cavity: a case report

Abstract: Background Schizophyllum commune is a basidiomycete that lives in the environment and can cause infections, mainly those of the respiratory system. Although S. commune is increasingly reported as a cause of allergic bronchopulmonary mycosis and sinusitis, cases of fungal ball formation are extremely uncommon. Identification of S. commune is difficult using routine mycological diagnostic methods, and in clinically suspicious cases, internal transcribed spacer sequencing should be used for diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Among the above discussed species, the species F. velutipes were characterized for HCs; the genus Malassezia was significantly abundant in the BP group; and genus Penicillium was significantly abundant in the LC group. Another species, Schizophyllum commune, which can cause respiratory system infections, was significantly enriched in the ILD group ( Itoh et al, 2021 ). The genus Pyrenophora was the character taxa in the FP group.…”
Section: Discussionmentioning
confidence: 99%
“…Among the above discussed species, the species F. velutipes were characterized for HCs; the genus Malassezia was significantly abundant in the BP group; and genus Penicillium was significantly abundant in the LC group. Another species, Schizophyllum commune, which can cause respiratory system infections, was significantly enriched in the ILD group ( Itoh et al, 2021 ). The genus Pyrenophora was the character taxa in the FP group.…”
Section: Discussionmentioning
confidence: 99%
“…Cases have reported that it can present with vascular and tissue invasion, as brain abscess and with pneumonia or as allergic bronchopulmonary mycosis in immunocompromised individuals. [6][7][8] Till date there is no single factor associated with S. commune infection, but it is mostly associated with young, male patients who are agricultural workers. In our patient, we noticed that it had occurred in an elderly female patient from an urban background.…”
Section: Discussionmentioning
confidence: 99%
“…During isolation of Saprolegnia species from the site of infection or water, some fungal contaminants may also be present. Some of the fungal species encountered were of Didymella, Phoma, Schizophyllum and Emmia which also produced white colonies [25] , [26] , [27] , [28] . Hence identification of Saprolegnia species based on culture morphology may be difficult for untrained eyes.…”
Section: Discussionmentioning
confidence: 99%